DESIGN AND MAKING OF INDUSTRY 4.0 READINESS MEASUREMENT SYSTEM FOR INDUSTRY IN INDONESIA - Caesar Ananta, Kevin
Evaluation of Industry 4.0 readiness is an important thing to do to understand the position of a company in the process of adapting the Industry 4.0 concept. To do this, a measuring tool that is able to measure the current condition of a company and indicate what must be applied or developed to achieve the expected Industry 4.0 application is needed. This study aims to design and create an Industry 4.0 readiness index measurement system that is able to measure the condition of Indonesian companies thoroughly. The stages of research carried out started with the literature study on Industry 4.0 concept, determinings the core concepts to form an understanding of Industry 4.0, deriving parameters and indicators based on the needs of the application of Industry 4.0, and evaluation and wight determination on the derived parameters. In the final stage of the research testing of the instruments is carried out through case studies of real conditions of several manufacturing industry companies in Indonesia. The output of this study is a set of measurement system that is able to evaluate state of a company in the process of adapting the Industry 4.0 concept accurately. The measurement result of a company’s state is also presented in quantative form of indexes ranging from zero to six.